2013
DOI: 10.1177/0163278713513949
|View full text |Cite
|
Sign up to set email alerts
|

Didactic Lecture Versus Interactive Workshop for Continuing Pharmacy Education on Reproductive Health

Abstract: Pharmacists are routinely providing reproductive health counseling in community pharmacies, but studies have revealed significant deficits in their competencies. Therefore, continuing pharmacy education (CPE) could be utilized as a valuable modality to upgrade pharmacists' capabilities. A randomized controlled trial was designed to compare the efficacy of CPE meetings (lecture based vs. workshop based) on contraception and male sexual dysfunctions. Sixty pharmacists were recruited for each CPE meeting. Small g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
14
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 24 publications
(34 reference statements)
2
14
0
Order By: Relevance
“…The brainstorming method might not be powerful enough to improve knowledge. Nevertheless, in our previous trial with short‐term exposure, we used a “simulated patient” technique, and the findings were similar to the present results . Mixed‐method training can be the most effective approach for 1‐day continuing education meetings .…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…The brainstorming method might not be powerful enough to improve knowledge. Nevertheless, in our previous trial with short‐term exposure, we used a “simulated patient” technique, and the findings were similar to the present results . Mixed‐method training can be the most effective approach for 1‐day continuing education meetings .…”
Section: Discussionsupporting
confidence: 87%
“…In our previous trials on continuing pharmacy education, we observed higher satisfaction with the interactive or mixed‐method instructional designs using the same satisfaction assessment tool . This finding was confirmed in the present study; nevertheless, we expected to see similar satisfaction with 3 items including “complying with previous knowledge,” “presenting up‐to‐date knowledge,” and “satisfying professional requirements” because the content of education was similar for both lecture and workshop groups.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…The speaker's ability to identify key issues, engage the audience and share their expertise will increase knowledge. [27,28] Our findings suggested lectures were more attended for up-to-date knowledge and CPD, although no statistical significant difference was found. Previous studies support this finding showing that workshops may not always be more effective than lectures.…”
Section: Discussionmentioning
confidence: 55%